The History of Translation of Malay Masterworks in China: (Sejarah Terjemahan Karya Melayu di China) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2015)
This paper discusses the history of the development of the translation of Malay works in China. Translations of Malay works published in China are first identified and then analysed by leveraging on the translation history approach by Pym (1998) and the bibliometric analysis method. In the period from 1985-2013, a total of seven Malay works from various literary genres were translated and published in China. Although not many in number, the total number of printed copies reached 20 000 nonetheless. This figure shows that Malay literature is relevant in the Chinese market. The translation industry of Malay works in China does not only depend on the collaboration of agencies in Malaysia, but China's own publication companies also take proactive measures. Better planning and a more active joint venture between Malaysia and China are crucial to the internationalizing of the Malay language and culture through translation.Keywords: Malay-Chinese translation, Malay literature, translation history